2022
DOI: 10.1073/pnas.2204306119
|View full text |Cite
|
Sign up to set email alerts
|

Early death in a mouse model of Alzheimer’s disease exacerbated by microglial loss of TAM receptor signaling

Abstract: Recurrent seizure is a common comorbidity in early-stage Alzheimer’s disease (AD) and may contribute to AD pathogenesis and cognitive decline. Similarly, many mouse models of Alzheimer’s disease that overproduce amyloid beta are prone to epileptiform seizures that may result in early sudden death. We studied one such model, designated APP/PS1 , and found that mutation of the TAM receptor tyrosine kinase (RTK) Mer or its ligand Gas6 greatly exacerbated early death. Lethality was tied to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 87 publications
0
5
0
Order By: Relevance
“…In the APP/PS1 mouse model of Alzheimer’s disease, Axl and MerTK have been shown to be important for microglia migration to amyloid plaques. 71 Genetic ablation of Axl and/or Mertk led to accelerated death of the animals, 72 indicative of a protective role for these receptors against disease progression. Longitudinal studies revealed that higher circulating levels of cleaved, soluble TAM receptors and their ligand GAS6 in the cerebrospinal fluid are associated with better cognitive outcome in Alzheimer’s disease.…”
Section: Discussionmentioning
confidence: 99%
“…In the APP/PS1 mouse model of Alzheimer’s disease, Axl and MerTK have been shown to be important for microglia migration to amyloid plaques. 71 Genetic ablation of Axl and/or Mertk led to accelerated death of the animals, 72 indicative of a protective role for these receptors against disease progression. Longitudinal studies revealed that higher circulating levels of cleaved, soluble TAM receptors and their ligand GAS6 in the cerebrospinal fluid are associated with better cognitive outcome in Alzheimer’s disease.…”
Section: Discussionmentioning
confidence: 99%
“…Since its inception, the contributions of the Lemke lab to the field of TAM biology have been extensive [ 10 , 37 , 45 , 48 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 ]. The phenotypic analysis of TAM receptor knockout mice provided early insights into the functional relevance of these receptors.…”
Section: The Lemke Lab Has Played a Major Role In Elucidating The Bio...mentioning
confidence: 99%
“…In studies focusing on microglial function in an animal model of Alzheimer’s disease (APP/PS1), ref. [ 60 ] the Lemke lab showed that the loss of either Mer or Gas6 exacerbated the number of animals that suffered early sudden death resulting from seizures. In these APP/PS1 mice, the seizures occur at a young age and are believed to be driven by activity in the dentate gyrus.…”
Section: The Lemke Lab Has Played a Major Role In Elucidating The Bio...mentioning
confidence: 99%
“…Such mechanisms also play an important role in maintaining excitatory:inhibitory (E:I) homeostasis in the cortical–hippocampal circuitry, which is prone to oAβ‐induced local excitotoxicity and hyperactivation in early‐stage AD 60,61 . The genetic ablation of critical immune and phagocytic regulators (e.g., IL‐18, Mer) in microglia can result in exuberant excitatory synaptic input in the hippocampus and cause lethal seizures in AD mouse models 62,63 . As such, epilepsy is an underappreciated comorbidity of AD in exacerbating hippocampal microgliosis 64–67 .…”
Section: Neurodegenrative Diseases and Agingmentioning
confidence: 99%
“…60,61 The genetic ablation of critical immune and phagocytic regulators (e.g., IL-18, Mer) in microglia can result in exuberant excitatory synaptic input in the hippocampus and cause lethal seizures in AD mouse models. 62,63 As such, epilepsy is an underappreciated comorbidity of AD in exacerbating hippocampal microgliosis. [64][65][66][67] Pharmaceutical prevention of seizures has been shown to improve cognitive performance in seizure-prone AD individuals.…”
Section: Alzheimer's Diseasementioning
confidence: 99%